2019
DOI: 10.5194/acp-19-2405-2019
|View full text |Cite
|
Sign up to set email alerts
|

Variability, timescales, and nonlinearity in climate responses to black carbon emissions

Abstract: Abstract. Black carbon (BC) particles exert a potentially large warming influence on the Earth system. Reductions in BC emissions have attracted attention as a possible means to moderate near-term temperature changes. For the first time, we evaluate regional climate responses, nonlinearity, and short-term transient responses to BC emission perturbations in the Arctic, midlatitudes, and globally based on a comprehensive set of emission-driven experiments using the Community Earth System Model (CESM). Surface te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…In the Arctic the effect of high-altitude BC is particularly strong, even causing a cooling at the surface for positive regional DRF, because of the strong vertical stability in this area (Flanner, 2013;Sand et al, 2013). A similar weaker temperature efficiency with stronger emission perturbations has also been found in Yang et al (2019), but for much higher emission perturbations. Figure 4a shows the climate sensitivity in terms of regional surface air temperature change per global DRF, i.e.…”
Section: Experimental Set-upmentioning
confidence: 59%
“…In the Arctic the effect of high-altitude BC is particularly strong, even causing a cooling at the surface for positive regional DRF, because of the strong vertical stability in this area (Flanner, 2013;Sand et al, 2013). A similar weaker temperature efficiency with stronger emission perturbations has also been found in Yang et al (2019), but for much higher emission perturbations. Figure 4a shows the climate sensitivity in terms of regional surface air temperature change per global DRF, i.e.…”
Section: Experimental Set-upmentioning
confidence: 59%
“…Finally, we do not have a definitive reference for the timedependent response to BC forcing perturbations. Instead, we compare the SCMs using the difference from the average of both MAGICC models, which both differentiate aerosol forcing between land and ocean, resulting in a faster overall climate response to aerosols compared to greenhouse gases (Shindell, 2014;Sand et al, 2016;Yang et al, 2019). In the case of BC, we note that all of the SCM responses should be taken critically because none show the fast temporal response to a BC step recently found in more complex models.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of BC, we note that all of the SCM responses should be taken critically because none show the fast temporal response to a BC step recently found in more complex models. An experiment using NorESM found a very short temporal response to a global step perturbation in black carbon (BC) with minimal long-term response (Sand et al, 2016) and with a similarly short timescale found for BC perturbations in the Arctic and midlatitudes (Yang et al, 2019). A more definitive evaluation of climate system responses to aerosol perturbations in general would be useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations